Financial Literacy, Lifestyle, and Financial Attitudes in Shaping Students’ Financial Behavior: Evidence from Mahasaraswati University, Denpasar - Nuho, Paula Noverita Sherenanda Ina Gawi; Gunadi, I Gusti Ngurah Bagus; Astiti, Ni Putu Yeni (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
Students are part of the young generation pursuing higher education who not only focus on seeking knowledge but also need to practice basic financial skills such as budgeting, daily savings planning, or long-term financial planning. In reality, there are still many students who have not yet implemented these activities. This study aims to examine the influence of financial literacy, financial attitudes, and lifestyle on the financial behavior of students at the Faculty of Economics and Business, Mahasaraswati University Denpasar. The population in this study was 4,108 active students at the Faculty of Economics and Business, Mahasaraswati University, Denpasar. The sampling method used in this study was the Slovin formula, so that the sample in this study was adjusted to 98 respondents. The data analysis techniques used in this study were multiple linear regression analysis, classical assumption test, F test, determination analysis, and t test. The results showed that financial literacy, financial attitude, and lifestyle each had a positive and significant effect on the financial behavior of students at the Faculty of Economics and Business, Mahasaraswati University, Denpasar. The financial behavior of students at the Faculty of Economics and Business, Mahasaraswati University, Denpasar, is explained by financial literacy, financial attitude, and lifestyle by only 53.0%, while 47.0% is influenced by other factors not included in the research model.